1996
DOI: 10.1055/s-2007-1006624
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Maximal Length of a Vein Conduit Used as an Interposition Graft for Nerve Regeneration

Abstract: Although autogenous veins have been used as nerve conduits (AVNCs) both experimentally and clinically for short nerve gaps up to 3 cm, investigators have not as yet determined the maximal effective length for functional nerve regeneration. In addition, the role of the distal nerve stump on subsequent nerve growth remains unclear. A rabbit peroneal nerve AVNC model was used to study axonal regeneration through nerve gaps of 1 to 6 cm. After allowing ample time for nerve regeneration, clinical, electophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 2 publications
2
44
0
5
Order By: Relevance
“…Even more sophisticated and long-term in vivo experiments have not obtained remarkable functional restoration [9,58]. The limitations in these approaches stem from several factors, like the restrictive cell response owing to activated astrocytes and macrophages [11,28,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more sophisticated and long-term in vivo experiments have not obtained remarkable functional restoration [9,58]. The limitations in these approaches stem from several factors, like the restrictive cell response owing to activated astrocytes and macrophages [11,28,59].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies aiming at the repair of nerve or brain tissue have been conducted with promising results, especially those which used cylindrical or tubular structures to mimic nervous tracts [9][10][11]. These anisotropic structures provide physical guidance for cell migration and axonal penetration and elongation and they permit the investigation of the effects of guidance stimuli to achieve efficient functional regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Most pretreatment methods, such as chemical treatment, irradiation, freezing, lyophilization, and freezethawing could effectively reduce nerve graft antigenicity; however, nerve regeneration remains inferior to autografts. One problem has been acellularizing the graft (Song, Yang, Russell, 2009), and although short nerve deficits (less than 3 cm) can be bridged by acellular grafts, longer deficits may be more dependent upon the presence of donor-derived viable SCs (Hems, Glasby, 1992;Evans et al, 1995;Strauch et al, 1996;Song, Yang, Russell, 2009), because viable SCs are essential for successful axonal regeneration through longer deficits (Hall, 1986;Feneley, Fawcett, Keynes, 1991;Bunge, 1993). Furthermore, Blais, Grenier, Berthod and Sun et al found that tissueengineered skin or acellular nerve allografts seeded with SCs could improve nerve regeneration (Blais, Grenier, Berthod, 2009;Sun et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When nerve defects exceed 3 cm, a vein conduit graft is less effective in maintaining the growth of nerve axons. 31 In a rabbit model it has been shown that nerve regeneration is enhanced by the distal stump of the transected nerve. This happens mainly because the distal stump of the nerve produces some key factors that promote nerve regeneration as nerve growth factor (NGF).…”
Section: Vein Graftsmentioning
confidence: 99%